Antimicrobial efficacy of the use of mouthwash with cetylpiridinium chloride for aerosol producing procedures : a systematic review = Eficacia antimicrobiana del uso del enjuague bucal concloruro de cetilpiridinio en procedimientos que generan aerosoles : revisión sistemática - Arce Toribio, Jackeline Paola
The present research aims to determine the antimicrobial efficacy of the mouthwashes based on cetylpyridinium chloride (CPC), before aerosol producing dental procedures. A data search was performed during August 2021 in five databases MEDLINE (PubMed), SCOPUS, SCIELO, Cochrane Central Register of Controlled Trials (CENTRAL) and Google Scholar. Randomized clinical trials (RCTs) were included based on the PICO question, comparing the efficacy of the mouthwashes based on cetylpyridinium chloride (CPC), versus other mouthwashes and water, before aerosol producing dental procedures, papers in English, Spanish and Portuguese were included without time limits. The risk of the included studies was evaluated with the tool RoB 2.0. Number of registration PROSPERO N° CRD42021275982. 120 papers were obtained in the preliminary search, discarding those that didn't comply with the selection criteria, leaving only 3 studies. These papers reported the use of cetylpyridinium chloride (CPC) was effective for the reduction of bacteria during the ultrasonic prophylactic procedure. The use of CPC mouthwashes previous to the dental treatment with ultrasonic prophylaxis showed only antibacterial capacity.